(untitled) (Web of Teachers: Inderscience Research, 2025)
Irony is a powerful tool for creating polysemy and multi-layered text. It allows the author to hide the true meaning of the statement, offering the reader to interpret it at different levels. In Russian literature, irony plays a key role, forming a double bottom of works and contributing to their deep comprehension. The article examines the role of irony in Russian literature on the example of the works of such writers as A. S. Pushkin, N. V. Gogol, F. M. Dostoevsky, L. N. Tolstoy, A. P. Chekhov and M. A. Bulgakov.